The relationship between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and rheumatoid arthritis: a cross-sectional study - Deng, Shuai; Qiu, Yijian; Wang, Qiang; Jiang, Jingjing; Xiang, Wang; Guo, Shifang; Yang, Shanggeng; Li, Encheng; Wu, Qingsong (Frontiers in Nutrition, 2025)
BackgroundResearch suggests a potential link between lipid metabolism and rheumatoid arthritis (RA). The ratio of non-high-density lipoprotein cholesterol (non-HDL-C) to high-density lipoprotein cholesterol (HDL-C) (NHHR) is a newly developed combined index to evaluate atherosclerotic lipids. This study aimed to explore the relationship between NHHR and the incidence rate of RA in the elderly in the United States.MethodsThis study analyzed data from the National Health and Nutrition Examination Survey (NHANES) collected between 2005 and 2018 to examine the association between NHHR levels and RA incidence, adopting multivariate logistic, subgroup analysis, and smooth curve analysis methods. Furthermore, the study investigated the potential mediating role of BMI and the use of statins in the RA-NHHR association through mediation analysis. The nonlinear aspect of the RA-NHHR relationship was explored using restricted cubic spline (RCS) analysis.ResultsThis study enrolled 6,433 participants, with a mean age of 69.9 years. Males accounted for 51% of the cohort, while females comprised 49%. Among them, 1,359 individuals reported a history of RA. A one-unit increment in NHHR was associated with an 11% reduction in the risk of RA. [Odds ratio (OR): 0.87; 95% CI: 0.81–0.92]. We have extensively adjusted for various confounding factors and still reflect the above relationship. Subgroup analysis (all p for interaction < 0.05) showed that age, gender, race, smoking, drinking, statins, and diabetes had no significant impact on this negative correlation. Mediation analysis revealed a significant intermediary effect of NHHR on RA through statins (p for trend<0.01). Lastly, the RCS findings indicated a substantial non-linear association between NHHR and RA (p-non-linear<0.05). Due to the cross-sectional nature of this study, it is not possible to determine the causal relationship. Therefore, in future studies, we can utilize other research designs, such as prospective cohort studies, to validate the temporal relationship between the two.ConclusionResearch has shown that NHHR levels are associated with a decrease in the incidence of rheumatoid arthritis in the elderly population in the United States. In addition, the linear relationship between RA and NHHR warrants further study.